DOP23 Decrements in quality of life associated with symptoms of Inflammatory Bowel Disease: results from the UK IBD-BOOST survey. (30th January 2023) - Roukas, C; Miller, L; Hamborg, T; Gordeev, V; Lindsay, J; Norton, C; Mihaylova, B
Abstract: Background: Inflammatory Bowel Disease (IBD) affects about 7 million people worldwide. People with active disease often experience symptoms of abdominal pain, fatigue and incontinence which may persist even in remission. We assess the impact of these symptoms, and the further contribution of anxiety and depression, on health-related quality of life (QoL) of people with IBD. Methods: In the IBD-BOOST survey, over 12, 500 people with IBD in the UK were approached across outpatient clinics, the IBD-BioResource participants and the Crohn's and Colitis UK charity membership; 8486 self-completed surveys were returned. Participants' QoL was measured using the EQ-5D-5L questionnaire, a generic health-related QoL instrument. Patients' QoL, ranging from 1 (perfect health) to -0.594 (worst health) was calculated using UK value set. Our approach involved three pre-specified stages of linear regression model development to assess the effects of symptoms on QoL. At stage 1 the model included IBD type, IBD activity score, IBD control score, socio-demographic characteristics and co-morbidities. At stage 2, the three key IBD symptoms: pain, fatigue and bowel incontinence were added. At stage 3, anxiety and depression were also included. Results: Table 1 presents selected characteristics of the 8486 IBD-BOOST survey participants (mean age 50 years, 58% women, 49% Crohn's disease). The EQ-5D-5L questionnaire was completed by 8114 (96%) participants reporting problems across QoL domains (Figure 1: 30% problems with mobility, 13% with self-care, 43% with usual activities, 60% pain/discomfort and 50% anxiety/depression). The mean QoL was 0.76 (SD 0.22). Health-related QoL was substantially reduced in respondents reporting higher IBD activity or worse IBD control (Table 2; stage 1). These associations weakened substantially following adjustment for the key IBD symptoms of pain, fatigue and bowel incontinence for which strong and graded associations with higher symptom severity associated with lower QoL were observed (Table 2; stage 2). The further inclusion of adjustments for anxiety and depression only moderately weakened previous associations and strong and graded associations between more severe anxiety or depression and lower QoL were also observed (Table 3; stage 3). Being male, obese, unemployed/retired, or having physical or mental health comorbidity were associated with lower QoL, and being in a relationship with higher QoL (results not shown). Conclusion: We report graded associations between symptoms of pain, fatigue, bowel incontinence, anxiety and depression and QoL in IBD. These estimates could inform assessments of interventions to improve IBD management.